Correlating histology and spectroscopy to differentiate pathologies of the colon - Carey, Duane; Shepherd, Neil A.; Kendall, Catherine; Stone, Nick; Breckon, Toby P.; Lloyd, Gavin Rhys (Cranfield University, 2012)
The techniques and procedures associated with histology are, in most cases, suitable for the diagnosis of colonic carcinomas. However, in cases such as epithelial misplacement the morphology of a stained tissue sample is homologous to that of cancer. This can lead to patients being misdiagnosed and undergoing unnecessary surgery. To prevent this surgery we suggest that the epithelium of tissue samples be examined using infrared (IR) spectroscopy. In this study, IR maps of tissue sections were registered to standard histology images so that epithelial specific spectra could be collected. The differences between these spectra were explored by using Principal Component Analysis (PCA). This paper provides a novel protocol detailing how histology specific spectra can be collected. The potential usefulness of these spectra is demonstrated through the separation of epithelial misplacement cases and colonic carcinomas within PCA space.
Keywords: automated microscopy